The Effect of Point L14 Acupressure Therapy on the Intensity of Labor Pain during the Active Phase I in Praktek Mandiri Bidan Bersama Kurao in 2023 - Islamela, Suci; Putri, Arfianingsih Dwi; Monarisa, Monarisa (Alifah Health Science Symposium Proceeding, 2023)
Labor pain is a physiological condition that occurs during the first stage of labor in the latent and active phases. Lots of mothers who give birth complain that they cannot bear the pain during labor so that they want to have a cesarean section. According to WHO (2019) the average standard for SC deliveries is around 5-15% per 1000 births in the world. According to data (Riskesdas) 2018 SC deliveries in Indonesia were 17.6% and in West Sumatra 14%. This study aims to determine the effect of point L14 acupressure therapy on the intensity of labor pain during the first active phase at PMB Bersama Kurao in 2023.The research method used is quantitative with a pre-experimental design. Data collection was carried out from April 5 until June 5 2023. The population of the study was all mothers with estimated give birth from April-June at PMB Bersama Kurao totaling 76 people. Sampling used the accidental sampling method totaling 30 mothers giving birth. Data was collected using a questionnaire. Data were analyzed using univariate and bivariate analysis with the Mann Whitney statistical test.The results showed that the intensity of labor pain at give birth mothers during the active phase I before and after being given acupressure therapy at point L14 are 7,37 and 6,00. Based on the results of Mann Whitney statistical tests, there was an effect of point L14 acupressure therapy on the intensity of labor pain in the active phase I (p-value = 0.000).It can be concluded that there is an effect of L14 point acupressure therapy on the intensity of active phase I labor pain at PMB Bersama Kurao. It is hoped that health workers will apply acupressure therapy to the L14 point to help reduce the intensity of pain in the active phase of labor in the first stage of labor as a form of caring for the mothers who give birth so that the mother feels calm and minimize trauma.